2012
DOI: 10.1029/2012jg001977
|View full text |Cite
|
Sign up to set email alerts
|

Regional‐scale phenology modeling based on meteorological records and remote sensing observations

Abstract: [1] Changes of vegetation phenology in response to climate change in the temperate forests have been well documented recently and have important implications on the regional and global carbon and water cycles. Predicting the impact of changing phenology on terrestrial ecosystems requires an accurate phenology model. Although species-level phenology models have been tested using a small number of vegetation species, they are rarely examined at the regional level. In this study, we used remotely sensed phenology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 100 publications
0
81
0
Order By: Relevance
“…1 in their general formulation have been proposed. These models rely on the use of low temperatures and photoperiods as main environmental cues and generally outperform threshold-type models (Delpierre et al 2009a;Yang et al 2012;Archetti et al 2013) but remain less accurate than budburst models, partially because the uncertainties associated with observed leaf senescence dates are considerably greater than the uncertainties regarding flowering and leaf unfolding dates.…”
Section: Modeling the Phenology Of Leaves And The Timing Of Floweringmentioning
confidence: 99%
“…1 in their general formulation have been proposed. These models rely on the use of low temperatures and photoperiods as main environmental cues and generally outperform threshold-type models (Delpierre et al 2009a;Yang et al 2012;Archetti et al 2013) but remain less accurate than budburst models, partially because the uncertainties associated with observed leaf senescence dates are considerably greater than the uncertainties regarding flowering and leaf unfolding dates.…”
Section: Modeling the Phenology Of Leaves And The Timing Of Floweringmentioning
confidence: 99%
“…Remote sensing imagery has been widely used over the past two decades for monitoring vegetation dynamics at regional to global scales in view of its synoptic coverage and repeated temporal sampling (Reed et al, 1994;Zhang et al, 2003;Julien and Sobrino, 2009;Yang et al, 2012;among many others). This approach also facilitates other kinds of studies that seek to explore the driving factors behind phenology change in the context of climate change Wang et al, 2011;Shen et al, 2011).…”
Section: H Liu Et Al: Soil Moisture Controls On Patterns Of Grass Gmentioning
confidence: 99%
“…An intercomparison of SOS retrieved using 10 satellite methods shows that the difference between individual methods can be as much as two months; and two methods were more closely related to ground observations than other methods [27]. Although validation against ground observations has been conducted for remotely sensed phenological metrics in many studies [5,13,14,26,27], the validation process is not standardized because the phenology-monitoring method usually varies among sites, and even the same dataset can be processed differently. More importantly, remotely sensed phenological metrics have not been evaluated in the context of DEMs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a comprehensive comparison of existing phenological models across geographic zones may help reduce the structural uncertainties [13]. Moreover, modeling studies at the regional scale demonstrated that, due to the difference in species type and composition, forests at different locations do not share common parameters, such as base temperature for growing degree day (GDD) calculation [13,14]. Thus, location-specific parameterization has the potential to reduce the uncertainty associated with model parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation